Incidence and risk factors associated with hypoglycemia in the first 48 hours of life in Small for Gestational Age Neonates - S., Alph Shirley; T., Antony Leo Jerry; R., Shiji (International Journal of Contemporary Pediatrics, 2018)
Background: Hypoglycemia is one of the important problems encountered in small for gestational age (SGA) neonates. The incidence and risk factors associated with hypoglycemia in the first 48 hours of life in Small for Gestational Age (SGA) Neonates was investigated in this study. Methods: Capillary Blood Glucose was screened by glucostix at 1, 2, 6, 12, 24, and 48 hours of age in 100 SGA neonates fulfilling the inclusion and exclusion criteria. Results: The overall incidence of hypoglycemia in SGA neonates in the study was 24%. The incidence of hypoglycemia was significantly higher in preterm SGA neonates (37.50%) when compared to term SGA neonates (17.65%). The incidence of symptomatic hypoglycemia was 9%. Maximum incidence of hypoglycemia was noted at 2 hours of life. Of the 24 SGA neonates with hypoglycemia, 33.33% had one episode of hypoglycemia, 45.83% had two episodes of hypoglycemia, 12.50% had three episodes of hypoglycemia, 8.33% had four episodes of hypoglycemia. None of the SGA neonate had more than four episodes of hypoglycemia. Early initiation of enteral feeding was significantly associated with decreased incidence of hypoglycemia in SGA neonates. There was no significant correlation between incidence of hypoglycemia in SGA neonates and gender of the baby, parity of mother, mode of delivery and type of IUGR. Conclusions: It is recommended to monitor all SGA neonates especially preterm SGA for hypoglycemia and ensure early initiation of enteral feeding in all SGA neonates.